Identifikasi Kebutuhan Masyarakat Nusa Tenggara Barat pada Pandemi Covid-19 di Media Sosial dengan Metode Crawling - Jian Budiarto (Puslitbang Sekawan Institute Nusa Tenggara, 2021)
People can write to the government about what they want through social media in the freedom of information era. Especially in the Covid-19 pandemic, the public's desire for government attention is getting higher. The purpose of this activity is to collect community needs at the beginning of the pandemic. The period of information retrieval is from March 30 to April 5, 2020. The activity uses the crawling method, which is gathering information with browser tools. The implementation stage starts from taking information with selenium, identifying posts and comments with Html tags, calculating the emergence of issues with N-gram NLP, and analyzing sentiment with Naive Bayes and Support-Vector Machine. The results showed that the community did not have panic to need foods with a total reaction of 172. The community was more worried about the spread of outbreaks from outside NTB with a reaction of 1,421.